1999
DOI: 10.1520/jfs14517j
|View full text |Cite
|
Sign up to set email alerts
|

Triacetone Triperoxide: Its Chemical Destruction

Abstract: Due to the known use of triacetone triperoxide (TATP) as an improvized explosive by terrorist organizations, it is essential that those involved in dealing with suspect materials should be aware of the characteristic properties of TATP, and have a means for disposing of it. This paper evaluates possible methods for disposing of TATP and describes in detail a convenient chemical reduction method. The risks involved in handling this sensitive explosive are shown to be considerably reduced by dissolving it in tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 4 publications
3
60
0
1
Order By: Relevance
“…In both solvents, acetone diperoxide (2a) showed lower rate constant values than some cyclic peroxides with bulkier substituents such as n-propyl or tert-butyl. Solvent effect studies of 1a have demonstrated that this compound is highly stable in solution [15], whereas in its solid state it shows a very different behavior that make possible its application as a primary explosive [16]. However, when the methyl group was replaced by ethyl (1b in Scheme 1) or the pentamethylene group (1c in Scheme 1) as substituent on the hexaoxacyclononane ring, the reactivity was substantially increased (Table V).…”
Section: Decomposition Of Pinacolone Cyclic Diperoxide (2c) In Pure Smentioning
confidence: 99%
“…In both solvents, acetone diperoxide (2a) showed lower rate constant values than some cyclic peroxides with bulkier substituents such as n-propyl or tert-butyl. Solvent effect studies of 1a have demonstrated that this compound is highly stable in solution [15], whereas in its solid state it shows a very different behavior that make possible its application as a primary explosive [16]. However, when the methyl group was replaced by ethyl (1b in Scheme 1) or the pentamethylene group (1c in Scheme 1) as substituent on the hexaoxacyclononane ring, the reactivity was substantially increased (Table V).…”
Section: Decomposition Of Pinacolone Cyclic Diperoxide (2c) In Pure Smentioning
confidence: 99%
“…[1][2][3] In this study a number of metal salts were used to attempt the destruction of TATP. When it was observed that they did not function alone, metal or acid was added to enhance reactivity.…”
Section: Destruction Of Thf Solutions Of Tatpmentioning
confidence: 99%
“…1,2 An attempt was made to promote room temperature reactivity with tin salts by adding metal and metal salts. While zinc or copper did not aid the action of the tin salts, zinc sulfate and copper chloride did (Table 3).…”
Section: Destruction Of Thf Solutions Of Tatpmentioning
confidence: 99%
“…It is very sensitive to impact, friction, static electricity, and temperature changes, particularly when stored as a dry product. TATP also rapidly sublimates (27).…”
Section: B Tatp and Hmtdmentioning
confidence: 99%